The Improvement of School Library Based on Accreditation in SMK Lugina Rancaekek - Agustine, Merryam; Aminudin; Rejeki, Diah Sri; Abinowi, Egi; Wahyuni, Haria Saputry (CENTRAL ASIA AND THE CAUCASUS, 2022)
The school library is a library organized in a school, managed, entirely by the school concerned, with the main objective of supporting the implementation and achievement of school goals and educational goals in general. The school library is a central source of knowledge and information in schools, both at the elementary level to the secondary level. The main objective of this paper is to know the improvement of school library based on accreditation. The subjects of this research are teachers who have a concern about school library, and the object of this research is the school library accreditation. The research method used is quantitative method. This research is divided into two levels, namely library as a building and library as a services. The results show that there are positive and significant results between the part of school library accreditation and the improvement of library as a building and there are positive and significant results between the part of school library accreditation and the improvement of library as a services.